Solve for y 3*(2y-5)-5(2y+4)=7-(y-2)

Math
3⋅(2y-5)-5(2y+4)=7-(y-2)
Simplify 3⋅(2y-5)-5(2y+4).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
3(2y)+3⋅-5-5(2y+4)=7-(y-2)
Multiply 2 by 3.
6y+3⋅-5-5(2y+4)=7-(y-2)
Multiply 3 by -5.
6y-15-5(2y+4)=7-(y-2)
Apply the distributive property.
6y-15-5(2y)-5⋅4=7-(y-2)
Multiply 2 by -5.
6y-15-10y-5⋅4=7-(y-2)
Multiply -5 by 4.
6y-15-10y-20=7-(y-2)
6y-15-10y-20=7-(y-2)
Simplify by adding terms.
Tap for more steps…
Subtract 10y from 6y.
-4y-15-20=7-(y-2)
Subtract 20 from -15.
-4y-35=7-(y-2)
-4y-35=7-(y-2)
-4y-35=7-(y-2)
Simplify 7-(y-2).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
-4y-35=7-y–2
Multiply -1 by -2.
-4y-35=7-y+2
-4y-35=7-y+2
Add 7 and 2.
-4y-35=-y+9
-4y-35=-y+9
Move all terms containing y to the left side of the equation.
Tap for more steps…
Add y to both sides of the equation.
-4y-35+y=9
Add -4y and y.
-3y-35=9
-3y-35=9
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 35 to both sides of the equation.
-3y=9+35
Add 9 and 35.
-3y=44
-3y=44
Divide each term by -3 and simplify.
Tap for more steps…
Divide each term in -3y=44 by -3.
-3y-3=44-3
Cancel the common factor of -3.
Tap for more steps…
Cancel the common factor.
-3y-3=44-3
Divide y by 1.
y=44-3
y=44-3
Move the negative in front of the fraction.
y=-443
y=-443
The result can be shown in multiple forms.
Exact Form:
y=-443
Decimal Form:
y=-14.6‾
Mixed Number Form:
y=-1423
Solve for y 3*(2y-5)-5(2y+4)=7-(y-2)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top